Konseling Lansia: Upaya Lanjut Usia dalam Membangun Kemandirian Hidup dan Penerimaan Diri Terhadap Kesiapan Memasuki Masa Pensiun (Studi Pada Lansia di Bina Keluarga Lansia Posyandu Cempaka Kabupaten Ngawi) - Diana Ariswanti Triningtyas; Siti Muhayati (JKI (Jurnal Konseling Indonesia), 2018)
In Indonesia, there are currently around 21 million elderly people or about 9.6% of the entire population of Indonesia. This shows that the Indonesian state has begun to belong to the aging population group. This research is motivated by the motivation of how to work for the elderly in building the independence of life. The purpose of the research is to describe and analyze the psychological impacts that affect the readiness to enter retirement, as well as how to build life independence and self-acceptance towards readiness to retire. The research design is qualitative descriptive. The sampling technique uses purposive sampling. Sources of data are obtained from informants, places, events and documents. Data collection techniques through participatory observation, in-depth interviews and documentation. Data analysis is carried out through stages, namely the data reduction stage, data presentation stage, and conclusions. Data validity, with technical triangulation, is by checking data to the same source with different techniques. The results of the study indicate that the independence of life of the elderly is relative. Psychological impacts that arise in the readiness to enter retirement for the elderly include aspects of health, economic aspects and social aspects. Understanding and building self-reliance and self-acceptance of readiness to retire in the Ngawi Cempaka Posyandu Family Elderly through Elderly Counseling.